Pareto-Efficient Tax Breaks - Sebastian Köhne; Dominik Sachs (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze Pareto-efficient tax breaks for work-related expenses in a Mirrleesian environment. Individuals are heterogenous in their ability. In addition to a labor-leisure choice, they decide how to spend their money between normal consumption and work-related goods. We derive an efficiency condition that relates the (implicit) subsidy rate for work-related goods to the marginal tax rate. Importantly, the condition holds irrespective of the skill distribution and the taste for redistribution. If the efficiency condition is violated, we show how to Pareto improve such allocations. For the special and policy-relevant case where goods contribute to the time available for market work (e.g., domestic services, child care or care for elderly relatives, health investment), we demonstrate that any tax system without a tax break for such goods can be improved in a Pareto sense. Pareto improvements are also possible if time-enhancing expenses are fully deductible from taxable income.
Keywords: D82; H21; 330; optimal taxation; tax deduction; Pareto improving tax reform